COMPUTER TRAINING AS A LEARNING SUPPLEMENT PAKET C IN PKBM SAUDARA SEJIWA DISTRICT OF DAYEUHKOLOT - Aneu Liana Dewi (STKIP Siliwangi, 2020)
The background of conducting this research is the need to strengthen the attractiveness of learning that can foster the learning appeal of PKBM Saudara Sejiwa in learning Paket C. The purpose of this study was to find out how computer training as a supplement to Paket C learning in the PKBM Saudara Sejiwa. The theoretical study used is the theory of out-of-school education, PKBM theory, equality theory, training theory, and learning theory. Researchers used qualitative descriptive methods to interview and observation techniques to obtain information from informants. The researcher took a random sample of one PKBM manager on the grounds that the manager's role affected the conditions in PKBM, one PKBM tutor, and three PKBM students PKBM Saudara Sejiwa because tutors and learners were directly involved in the computer learning process. The results of the research at PKBM Saudara Sejiwa is that computer training as a supplement to learning the Paket C of PKBM Saudara Sejiwa has been running well, seen from the benefits and encouragement of students to participate in training activities, although constrained by the division of time between training and student work. Conclusion This study is that computer training as a supplement to Paket C learning at PKBM Saudara Sejiwa has been running as it should or according to the needs of students. Seen from the number of graduates who are unemployed. Computer training is a good learning supplement because, computer training is part of the process of learning and the principles of training are developed into learning for Paket C students at the PKBM Saudara Sejiwa.